Proposal of a multimodal robotic architecture considering social constraints applied to an intelligent wheelchair - Moitinho, Vinícius; Brito, Felix; Diaz-Amado, Jose; Costa, Vitor; Sousa, Daniel; Prado, Elvio; Libarino, Cleia; Soares, João Erivandro (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Autonomous wheelchairs significantly facilitate the routine of people who depend on this equipment to get around. Therefore, they must consist of algorithms and components of perception and control, which allow interaction with the external environments where they are inserted and also with the wheelchair user. However, these components and algorithms need to collaborate with each other in order for the wheelchair to function properly, and because of this, it is of utmost importance that there is an architectural development stage of the design of systems like this. Software architectures realize the structure and organization of the components, which makes it easier to make decisions regarding the distribution of the system. With this in mind, this paper describes a software architecture developed for an autonomous intelligent wheelchair. The main goal of this architecture is to enable the operation of the robotic system of the wheelchair so that it can navigate independently, taking into account the social constraints of human interaction. To achieve this purpose, several software architecture models of different types of autonomous systems were researched in order to integrate them into the development of the project. It was observed that an architecture arranged in layers would be the best option for the project in question. Thus, a six-layered software architecture was developed, which resulted in the implementation of a multimodal system for an intelligent wheelchair. The main contribution of this article is the association between human social restrictions and the functioning of autonomous service systems in a software architecture.